Trend Technological Pedagogical and Content Knowledge to Improve Biology Teacher Competency in the 21st Century: A Review - Tanta (Postgraduate, University of Mataram, 2024)
Biology teachers may use technology to improve learning outcomes and design engaging learning experiences for students in the digital age by becoming proficient and competent in TPACK. Previous researchers have used TPACK to improve teacher competency, namely found that fusing technology, pedagogy, and topic knowledge, significantly improves teacher proficiency. Studies have indicated that teachers gain from TPACK training, which raises their competency levels. TPACK raises teachers' competencies in teaching and learning processes by requiring them to possess a thorough understanding of technology operations, pedagogical skills, and topic knowledge The research aims to explore and highlight several research publications that examine TPACK to improve Biology teacher competency in the 21st century. A systematic literature review method was used to select relevant articles for review, with a total of 25 articles selected based on specific criteria for the literature review stage. The research results highlight the importance of integrating TPACK to improve biology teacher competency. This integration aims to equip educators with the skills necessary to effectively apply technology in biology teaching in the 21st century. The conclusion drawn is that TPACK can improve the competence of biology teachers in the 21st century to design interesting learning experiences for students.